2010
DOI: 10.1159/000320274
|View full text |Cite
|
Sign up to set email alerts
|

Serum Adipocytokine and Vascular Inflammation Marker Levels in Beta-Thalassaemia Major Patients

Abstract: Background/Aim: The adipocytokines leptin and adiponectin represent a critical link between metabolism, immunity and chronic inflammation. A chronic vascular inflammatory state plays an important role in the pathophysiology of thalassaemia. We aimed to analyze the levels of these adipocytokines and determine any possible correlations with disease severity or vascular inflammation markers in beta-thalassaemia. Methods: Serum leptin, adiponectin, high-sensitivity C-reactive protein, endothelins, vascular adhesio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
23
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 52 publications
(34 reference statements)
4
23
2
Order By: Relevance
“…This was matched with previous studies [14,16,18]. Increasing evidence supports the role of inflammation in the pathogenesis of complications in β-thalassaemia, a genetic haematological disease.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This was matched with previous studies [14,16,18]. Increasing evidence supports the role of inflammation in the pathogenesis of complications in β-thalassaemia, a genetic haematological disease.…”
Section: Discussionsupporting
confidence: 90%
“…Elsayh et al's [16], study on 35 patients with β-thalassaemia major patients, reported positive correlation between adiponectin and highly senstive CRP (hsCRP). In contrast, Chaliasos et al's [14], study on 28 patients with β-thalassaemia major patients did not found significant correlation between serum adiponectin and CRP. Linear regression analysis revealed that IL-6 was an independent predictor of adiponectin level.…”
Section: Discussionmentioning
confidence: 77%
“…P < 0.01 the relation is statistically highly significant. This is in agreement with that reported in other studies, which found that adiponectin, resistin, and visfatin concentrations were significantly higher in both b-thalassemia intermedia and BTM patients compared with controls and speculated that these adipocytokines may play a role in the development of complications in b-thalassemia [20,21].…”
Section: Discussionsupporting
confidence: 93%
“…A growing number of studies have examined the potential role of different inflammatory, endothelial adhesion molecules (sVCAM-1 and sICAM-1) and adipocytokines (adiponectin, resistin, and visfatin) in thalassemia, suggesting the potential role of these markers in the development of inflammation and complications in b-thalassemia [15,20,21].…”
Section: Discussionmentioning
confidence: 99%
“…60,61 This proposed model of pulmonary vasculopathy promoted by iron burden is of general interest in light of other studies suggesting that iron promotes systemic endothelial dysfunction and atherosclerosis in patients without SCD 62,63 and suggests that these pathways each comprise elements of systemic vasculopathy. These pathways are likely to pertain also to b-thalassemia major, 64,65 another hemoglobinopathy with transfusion-associated iron overload and prevalent pulmonary hypertension. 66 Figure 5.…”
Section: Discussionmentioning
confidence: 99%